A systematic review on technology-based instructions to develop English pragmatic competence for non-native speakers - Hui, Xianxin; Liu, Zhifang; Chi, Yongmei (International Journal of Evaluation and Research in Education (IJERE), 2024)
With the rapid development of world Englishes (WEs) and multilingualism, pragmatic failure is still an unsolved matter for non-native speakers (NNSs). Although many studies have paid attention to technology application in second language acquisition (SLA), there are limited systematic reviews concerning technology-based instructions to develop English pragmatic competence for NNSs. This study gains a comprehensive overview to identify the situation and trend of technology-based instructions to develop English pragmatic competence for NNSs based on 20 articles from 2015 to 2023. Various findings indicate that based on technology instructions and technology resources, English pragmatic awareness and multidimensional development should be emphasized to foster English pragmatic competence among NNSs. Implications and suggestions are also provided for further research from this review.